The Essentials of Cardiac Computerized Tomography. Issue 2 (December 2015) - McKavanagh, Peter; Walls, Gerard; McCune, Claire; Malloy, Jonathon; Harbinson, Mark; Ball, Peter; Donnelly, Patrick
Abstract Cardiac computerized tomography (CT) has evolved from a research tool to an important diagnostic investigation in cardiology, and is now recommended in European, US, and UK guidelines. This review is designed to give the reader an overview of the current state of cardiac CT. The role of cardiac CT is multifaceted, and includes risk stratification, disease detection, coronary plaque quantification, defining congenital heart disease, planning for structural intervention, and, more recently, assessment of ischemia. This paper addresses basic principles as well as newer evidence.